PENERAPAN MODEL PEMBELAJARAN TARI BAMBU TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII SMP N 3 SUNGAI LALA - Mustika, Helma; Surianto, Bambang (Universitas Muhammadiyah Bengkulu, 2019)
The purpose of this study was to determine the ability to understand the concept with learning Bamboo Dance better than the ability to understand the concept with conventional learning VII grade students of SMP N 03 Sungai Lala. The type of this research is experimental research, with class VII B as an experimental class totaling 26 students and VII Â A as a control class with 25 students, the research design used was Randomized Subjects posttes only control group design. The results of the calculation of the hypothesis test obtained thitung = 3.159 and t table = 2.009. Because thitung is in the rejection area of H0, meaning that the average understanding ability of students' mathematical concepts with the application of the Bamboo Dance model is better than the average ability to understand mathematical concepts of students with conventional learning on line and angle material in class VII of Sungai Lala SMP Negeri 3.Keywords: Understanding the concept, Bamboo Dancing